Synthesis of Novel N, N'-Diphenyl-1, 3-Benzene-bis-Carbohydrazonoyl Bromide and its Utility in Facile Synthesis of New 1, 3-Pheneylene Bridged bis-Heterocycles. (26th May 2020) - Hassaneen, Hamdi M.; Abdallah, Tayseer A.; Saleh, Fatma M.; Sh. Mohamed, Yasmin; Awad, Enas M.
Abstract: Reaction of N, N'-diphenyl-1, 3-benzene- bis -carbohydrazonoyl bromide 3 with potassium thiocyanate, potassium selenocyanate, active methylene compounds and dipolarophilic alkenes were studied. Structures of the products were established on analytical and spectral data as well as chemical transformations. The results indicated that compound 3 is useful precursor for synthesis of a wide variety of 1, 3-phenylene- bis -heterocycles.